(3fSHI GdNQbI hTQhWgGs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NdY Ydi YHGOg Cgd GdYfGjI CSeGDg GdMSfi djMdge HPdc GdeMd GdCTQa Ke bGd dge dJYdehG Cfg ef cGf efG dGjLhR dg s
(3BNQgG (B:s
(3WQjb CNQi dfG UMHJ CfG GdNVQYdjg GdSdGe hJCOHJ Hg jG UahI GdOjf CfJ GdOjf CLeYg WGHJ HPcQc CYQGa hCahGg Je GdLRA hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs